Tinjauan Integratif Fiqh dan Sosial terhadap Fenomena Murtad di Indonesia - Nurul Wahyuni; Zainuddin Zainuddin (ISLAMIKA, 2023)
This study examines the review of the integration of fiqh and social towards the phenomenon of apostasy in Indonesia. The problem is that the phenomenon of apostasy in Indonesia is increasing, while religious doctrine, especially Islam, does not tolerate such apostate behavior. From these problems, research questions arise: 1) How does society react to apostates? 2) What are the implications of apostasy in social life? This research is a field research using a qualitative approach. Data was collected through interviews with 20 informants, tracking online media and print media such as social media, Google, news on online sites, and Youtube to collect information relevant to apostates in a review of fiqh and social integration. The data collected was analyzed using descriptive analysis techniques which will be presented in order to answer the problems. Based on the results of the study it was found that in the problem of apostasy there is a significant integration of fiqh and social. This can be seen from the impact/implications arising from the act of apostasy in a fiqh and social review, namely being the cause of a person's apostasy through a study of fiqh and social facts, apostasy being the cause of rifts in the family, being a hindrance to child custody, and being the cause of a couple's divorce. husband and wife, as well as the reaction of an indigenous community that advises apostates to return to Islam is also taught in fiqh and social matters.